2008
DOI: 10.5380/rsa.v9i1.10141
|View full text |Cite
|
Sign up to set email alerts
|

Substratos E Auxinas No Enraizamento De Estacas Caulinares De Espinheira-Santa

Abstract: A espinheira-santa (Maytenus ilicifolia) é uma planta medicinal cujas folhas são utilizadas no tratamento de úlceras gástricas, mas apesar de sua importância, são poucas as informações publicadas sobre a produção de mudas e técnicas de propagação vegetativa da espécie. Este trabalho teve por objetivo avaliar o enraizamento de estacas caulinares de espinheira-santa submetidas à aplicação de duas auxinas, em dois substratos. Estacas caulinares semilenhosas foram preparadas com uma folha e 1 cm de caule, e caulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
0
11
0
3
Order By: Relevance
“…Lima et al (2008), studying the effect of IBA doses on different substrates on the layering of Maytenus muelleri, did not obtain rooting for any of the tested substrates, including coconut fiber and sphagnum. It can be inferred, therefore, that different species show different responses to different substrates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lima et al (2008), studying the effect of IBA doses on different substrates on the layering of Maytenus muelleri, did not obtain rooting for any of the tested substrates, including coconut fiber and sphagnum. It can be inferred, therefore, that different species show different responses to different substrates.…”
Section: Resultsmentioning
confidence: 99%
“…At this same dose of IBA, the percentage of callus formation was 100% for all other substrates evaluated. Lima et al (2008), studying the substrates sphagnum, coconut fiber and vermiculite in propagation by layering of "espinheira-santa" (Maytenus muelleri), found that the percentage of layers with callus was significantly higher when used coconut fiber (49%), while the sphagnum provided a smaller percentage of layers with callus (13%).…”
Section: The Lychee Tree Propagation By Layeringmentioning
confidence: 99%
“…Recent studies showed that HA stimulate the activity and synthesis of H + -ATPase enzymes in the plasma membrane of plant cells, similarly to the auxinic effect (Canellas et al 2006). Synthetic auxins, known as plant growth regulators (Taiz & Zeigher, 2003), are used on a commercial scale to promote rooting of ornamental plants (Vieira & Castro, 2001;Lima et al, 2008). Application of HA, the bioactive fraction of the humified organic matter, to produce spikes and commercial corms, is another technological option.…”
Section: Introductionmentioning
confidence: 99%
“…The indolbutyric acid (IBA) is a synthetic auxin used to promote rooting of ornamental plants on a commercial scale (Lima et al, 2008, Hartmann et al, 2011.…”
Section: Introductionmentioning
confidence: 99%